Digital urbanism in a transitional economy – a review of India's municipal e-governance policy. Issue 3 (2nd September 2018) - Chatterji, Tathagata
ABSTRACT: The basic premise of India's new urban agenda rests on widespread application Information Technology (IT) tools to improve the quality of data infrastructure, services delivery and citizen interface in existing cities. These digital urban projects are being rolled out through a complex multilayered partnership arrangement between the state agencies, the corporate sector and international agencies. This paper analyses implementation challenges of this technocentric top-down urban agenda, due to sharp spatio-economic digital divide and institutional capacity deficits. Years of neglect had made the India's municipal bodies weak and suffer skilled human resource shortage in the areas of IT and e-governance. The paper argues that unless the e-governance applications are internalized by the elected municipal bodies, it can result in gradual outsourcing of municipal governance and reduce opportunities for public participation in local governance. Moreover, digital literacy and network infrastructure require substantial strengthening in small- and medium-sized cities, to avoid further digital polarization.